2021
DOI: 10.3390/antiox10091480
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Treatment Is Insufficient to Inactivate SARS-CoV-2 Surrogate under Field Conditions

Abstract: COVID-19 caused by SARS-CoV-2 caused a worldwide crisis, highlighting the importance of preventive measures in infectious diseases control. SARS-CoV-2 can remain infectious on surfaces for up to several weeks; therefore, proper disinfection is required to mitigate the risk of indirect virus spreading. Gaseous ozone treatment has received particular attention as an easily accessible disinfection tool. In this study, we evaluated the virucidal effectiveness of gaseous ozone treatment (>7.3 ppm, 2 h) on MHV-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Ozone treatment was found to be more beneficial than usual care in COVID-19 patients with severe respiratory symptoms ( 35 ). According to Franzini’s research, O2 saturation increased from 85 to 95% after an 8.6-day ozone treatment ( 13 ). Araimo also discovered that the demand for ventilator support was moderately reduced in the ozone group (reduced need for CPAP, high-flow nasal cannula, or venturi masks) ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone treatment was found to be more beneficial than usual care in COVID-19 patients with severe respiratory symptoms ( 35 ). According to Franzini’s research, O2 saturation increased from 85 to 95% after an 8.6-day ozone treatment ( 13 ). Araimo also discovered that the demand for ventilator support was moderately reduced in the ozone group (reduced need for CPAP, high-flow nasal cannula, or venturi masks) ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ozone reduces inflammation by acting on interleukins, raises ATP in red blood cells, and enhances RBCs’ access to oxygen ( 12 ). Additionally, it is an excellent biocidal agent due to its strong oxidizing properties, and its effectiveness has been confirmed in bacteria, fungi, and viruses ( 13 ). Ozone can have great potential for improving oxygenation in COVID-19 patients due to its antioxidant, antiviral, and anti-inflammatory characteristics ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth pointing out that some studies have demonstrated the ineffectiveness of ozone against certain viruses (HIV-1, HBV, EV71, MHV) [179] , [180] , [181] , [182] . A possible reason for this observation is ozone consumption by the culture media (required by the cells that harbour the virus); thus making reducing ozone’s availability for inactivation of the virus.…”
Section: Ozone In the Era Of Covid-19mentioning
confidence: 99%
“…Ozone being an unstable molecule can break up into its split products, namely reactive oxygen species and ozonides, creating a toxic environment for these viruses [112][113][114]. Some authors (Mazur-Panasiuk et al 2021) [115] are skeptical about the effectiveness of this method for food transport. Unwanted fluctuations in temperature as well as other parameters (e.g., humidity and air composition) can be mitigated by combining appropriate simple statistical tools with new technology of measuring temperature and/or other physical variables and recording them, as the latter is described below.…”
Section: Management Of Temperature In the Fcc Augmented With Spcmentioning
confidence: 99%